Rumah Orang Huaulu, Pulau Seram Maluku Tengah - Lucas Wattimena (Kapata Arkeologi, 2015)
House of Huaulu, Seram Island in Central Mollucas district has several aspects related to the pattern of the building, the building materials used, as well as the pattern of worked. The purpose of this researches is to known and understand what kind of aspects are contained in the house of Huaulu People. The method uses ethnoarcheology approach, the data collection techniques interview, observation and literature study. The analysis was performed by descriptive follow aspects of ethnoarchaeology. The results showed that the House of Huaulu People, has two aspects. First aspect of knowledge covering the level of understanding in working on the house, the house view of the cosmos, as well as the art of decorative patterns that interpret the cultural social life. Second, the technological aspect is the level of knowledge and understanding of the tools and materials used for the construction of the house.Rumah Orang Huaulu, Pulau Seram Kabupaten Maluku Tengah memiliki beberapa aspek yang terkait dengan pola bangunan, bahan bangunan yang digunakan, serta pola pengerjaannya.Tujuan penelitian untuk mengetahui dan memahami aspek-aspek apa saja yang terdapat pada rumah Orang Huaulu. Metode menggunakan  pendekatan etnoarkeologi, dengan teknik pengumpulan data wawancara, observasi dan studi kepustakaan. Analisis dilakukan secara deskriptif mengikuti aspek-aspek dalam Etnoarkeologi. Hasil penelitian menunjukan bahwa Rumah Orang Huaulu memiliki dua aspek. Pertama aspek pengetahuan meliputi tingkat pemahaman dalam mengerjakan rumah, pandangan terhadap kosmos rumah, serta seni pola hias yang menginterprestasikan kehidupan sosial budayanya. Kedua, Aspek teknologi yaitu tingkat pengetahuan dan pemahaman tentang alat dan bahan yang digunakan untuk pengerjaan rumah.